Partial enumeration and curvature regularization - Olsson, Carl; Ulen, Johannes; Boykov, Yuri; Kolmogorov, Vladimir
Energies with high-order non-submodular interactions have been shown to be very useful in vision due to their high modeling power. Optimization of such energies, however, is generally NP-hard. A naive approach that works for small problem instances is exhaustive search, that is, enumeration of all possible labelings of the underlying graph. We propose a general minimization approach for large graphs based on enumeration of labelings of certain small patches. This partial enumeration technique reduces complex high-order energy formulations to pairwise Constraint Satisfaction Problems with unary costs (uCSP), which can be efficiently solved using standard methods like TRW-S. Our approach outperforms a number of existing state-of-the-art algorithms on well known difficult problems (e.g. curvature regularization, stereo, deconvolution); it gives near global minimum and better speed. Our main application of interest is curvature regularization. In the context of segmentation, our partial enumeration technique allows to evaluate curvature directly on small patches using a novel integral geometry approach.

Morpho-physiological criteria divide dentate gyrus interneurons into classes - Hosp, Jonas; Strüber, Michael; Yanagawa, Yuchio; Obata, Kunihiko; Vida, Imre; Jonas, Peter M; Bartos, Marlene (Hippocampus)
GABAergic inhibitory interneurons control fundamental aspects of neuronal network function. Their functional roles are assumed to be defined by the identity of their input synapses, the architecture of their dendritic tree, the passive and active membrane properties and finally the nature of their postsynaptic targets. Indeed, interneurons display a high degree of morphological and physiological heterogeneity. However, whether their morphological and physiological characteristics are correlated and whether interneuron diversity can be described by a continuum of GABAergic cell types or by distinct classes has remained unclear. Here we perform a detailed morphological and physiological characterization of GABAergic cells in the dentate gyrus, the input region of the hippocampus. To achieve an unbiased and efficient sampling and classification we used knock-in mice expressing the enhanced green fluorescent protein (eGFP) in glutamate decarboxylase 67 (GAD67)-positive neurons and performed cluster analysis. We identified five interneuron classes, each of them characterized by a distinct set of anatomical and physiological parameters. Cross-correlation analysis further revealed a direct relation between morphological and physiological properties indicating that dentate gyrus interneurons fall into functionally distinct classes which may differentially control neuronal network activity.

Universality of general β-ensembles - Erdös, László; Bourgade, Paul; Yau, Horng (Duke Mathematical Journal)
We prove the universality of the β-ensembles with convex analytic potentials and for any β > 0, i.e. we show that the spacing distributions of log-gases at any inverse temperature β coincide with those of the Gaussian β-ensembles.

Strategy synthesis for multi-dimensional quantitative objectives - Chatterjee, Krishnendu; Randour, Mickael; Raskin, Jean (Acta Informatica)
Multi-dimensional mean-payoff and energy games provide the mathematical foundation for the quantitative study of reactive systems, and play a central role in the emerging quantitative theory of verification and synthesis. In this work, we study the strategy synthesis problem for games with such multi-dimensional objectives along with a parity condition, a canonical way to express ω ω -regular conditions. While in general, the winning strategies in such games may require infinite memory, for synthesis the most relevant problem is the construction of a finite-memory winning strategy (if one exists). Our main contributions are as follows. First, we show a tight exponential bound (matching upper and lower bounds) on the memory required for finite-memory winning strategies in both multi-dimensional mean-payoff and energy games along with parity objectives. This significantly improves the triple exponential upper bound for multi energy games (without parity) that could be derived from results in literature for games on vector addition systems with states. Second, we present an optimal symbolic and incremental algorithm to compute a finite-memory winning strategy (if one exists) in such games. Finally, we give a complete characterization of when finite memory of strategies can be traded off for randomness. In particular, we show that for one-dimension mean-payoff parity games, randomized memoryless strategies are as powerful as their pure finite-memory counterparts.

Persistent homology: Theory and practice - Edelsbrunner, Herbert; Morozovy, Dmitriy
Persistent homology is a recent grandchild of homology that has found use in science and engineering as well as in mathematics. This paper surveys the method as well as the applications, neglecting completeness in favor of highlighting ideas and directions.

Interface simulation distances - Cerny, Pavol; Chmelik, Martin; Henzinger, Thomas A; Radhakrishna, Arjun (Theoretical Computer Science)
The classical (boolean) notion of refinement for behavioral interfaces of system components is the alternating refinement preorder. In this paper, we define a distance for interfaces, called interface simulation distance. It makes the alternating refinement preorder quantitative by, intuitively, tolerating errors (while counting them) in the alternating simulation game. We show that the interface simulation distance satisfies the triangle inequality, that the distance between two interfaces does not increase under parallel composition with a third interface, that the distance between two interfaces can be bounded from above and below by distances between abstractions of the two interfaces, and how to synthesize an interface from incompatible requirements. We illustrate the framework, and the properties of the distances under composition of interfaces, with two case studies.

Efficient and dynamic algorithms for alternating Büchi games and maximal end-component decomposition - Chatterjee, Krishnendu; Henzinger, Monika H (Journal of the ACM)
The computation of the winning set for Büchi objectives in alternating games on graphs is a central problem in computer-aided verification with a large number of applications. The long-standing best known upper bound for solving the problem is Õ(n ⋅ m), where n is the number of vertices and m is the number of edges in the graph. We are the first to break the Õ(n ⋅ m) boundary by presenting a new technique that reduces the running time to O(n2). This bound also leads to O(n2)-time algorithms for computing the set of almost-sure winning vertices for Büchi objectives (1) in alternating games with probabilistic transitions (improving an earlier bound of Õ(n ⋅ m)), (2) in concurrent graph games with constant actions (improving an earlier bound of O(n3)), and (3) in Markov decision processes (improving for m>n4/3 an earlier bound of O(m ⋅ √m)). We then show how to maintain the winning set for Büchi objectives in alternating games under a sequence of edge insertions or a sequence of edge deletions in O(n) amortized time per operation. Our algorithms are the first dynamic algorithms for this problem. We then consider another core graph theoretic problem in verification of probabilistic systems, namely computing the maximal end-component decomposition of a graph. We present two improved static algorithms for the maximal end-component decomposition problem. Our first algorithm is an O(m ⋅ √m)-time algorithm, and our second algorithm is an O(n2)-time algorithm which is obtained using the same technique as for alternating Büchi games. Thus, we obtain an O(min &lcu;m ⋅ √m,n2})-time algorithm improving the long-standing O(n ⋅ m) time bound. Finally, we show how to maintain the maximal end-component decomposition of a graph under a sequence of edge insertions or a sequence of edge deletions in O(n) amortized time per edge deletion, and O(m) worst-case time per edge insertion. Again, our algorithms are the first dynamic algorithms for this problem.

Adaptation to changes in higher-order stimulus statistics in the salamander retina - Tkacik, Gasper; Ghosh, Anandamohan; Schneidman, Elad; Segev, Ronen (PLoS One)
Adaptation in the retina is thought to optimize the encoding of natural light signals into sequences of spikes sent to the brain. While adaptive changes in retinal processing to the variations of the mean luminance level and second-order stimulus statistics have been documented before, no such measurements have been performed when higher-order moments of the light distribution change. We therefore measured the ganglion cell responses in the tiger salamander retina to controlled changes in the second (contrast), third (skew) and fourth (kurtosis) moments of the light intensity distribution of spatially uniform temporally independent stimuli. The skew and kurtosis of the stimuli were chosen to cover the range observed in natural scenes. We quantified adaptation in ganglion cells by studying linear-nonlinear models that capture well the retinal encoding properties across all stimuli. We found that the encoding properties of retinal ganglion cells change only marginally when higher-order statistics change, compared to the changes observed in response to the variation in contrast. By analyzing optimal coding in LN-type models, we showed that neurons can maintain a high information rate without large dynamic adaptation to changes in skew or kurtosis. This is because, for uncorrelated stimuli, spatio-temporal summation within the receptive field averages away non-gaussian aspects of the light intensity distribution.

Qualitative concurrent parity games: Bounded rationality - Chatterjee, Krishnendu (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We study two-player concurrent games on finite-state graphs played for an infinite number of rounds, where in each round, the two players (player 1 and player 2) choose their moves independently and simultaneously; the current state and the two moves determine the successor state. The objectives are ω-regular winning conditions specified as parity objectives. We consider the qualitative analysis problems: the computation of the almost-sure and limit-sure winning set of states, where player 1 can ensure to win with probability 1 and with probability arbitrarily close to 1, respectively. In general the almost-sure and limit-sure winning strategies require both infinite-memory as well as infinite-precision (to describe probabilities). While the qualitative analysis problem for concurrent parity games with infinite-memory, infinite-precision randomized strategies was studied before, we study the bounded-rationality problem for qualitative analysis of concurrent parity games, where the strategy set for player 1 is restricted to bounded-resource strategies. In terms of precision, strategies can be deterministic, uniform, finite-precision, or infinite-precision; and in terms of memory, strategies can be memoryless, finite-memory, or infinite-memory. We present a precise and complete characterization of the qualitative winning sets for all combinations of classes of strategies. In particular, we show that uniform memoryless strategies are as powerful as finite-precision infinite-memory strategies, and infinite-precision memoryless strategies are as powerful as infinite-precision finite-memory strategies. We show that the winning sets can be computed in (n2d+3) time, where n is the size of the game structure and 2d is the number of priorities (or colors), and our algorithms are symbolic. The membership problem of whether a state belongs to a winning set can be decided in NP ∩ coNP. Our symbolic algorithms are based on a characterization of the winning sets as μ-calculus formulas, however, our μ-calculus formulas are crucially different from the ones for concurrent parity games (without bounded rationality); and our memoryless witness strategy constructions are significantly different from the infinite-memory witness strategy constructions for concurrent parity games.

Robust multi-property combiners for hash functions - Fischlin, Marc; Lehmann, Anja; Pietrzak, Krzysztof Z (Journal of Cryptology)
A robust combiner for hash functions takes two candidate implementations and constructs a hash function which is secure as long as at least one of the candidates is secure. So far, hash function combiners only aim at preserving a single property such as collision-resistance or pseudorandomness. However, when hash functions are used in protocols like TLS they are often required to provide several properties simultaneously. We therefore put forward the notion of robust multi-property combiners and elaborate on different definitions for such combiners. We then propose a combiner that provably preserves (target) collision-resistance, pseudorandomness, and being a secure message authentication code. This combiner satisfies the strongest notion we propose, which requires that the combined function satisfies every security property which is satisfied by at least one of the underlying hash function. If the underlying hash functions have output length n, the combiner has output length 2 n. This basically matches a known lower bound for black-box combiners for collision-resistance only, thus the other properties can be achieved without penalizing the length of the hash values. We then propose a combiner which also preserves the property of being indifferentiable from a random oracle, slightly increasing the output length to 2 n+ω(log n). Moreover, we show how to augment our constructions in order to make them also robust for the one-wayness property, but in this case require an a priory upper bound on the input length.

First cycle games - Aminof, Benjamin; Rubin, Sasha (Electronic Proceedings in Theoretical Computer Science, EPTCS)
First cycle games (FCG) are played on a finite graph by two players who push a token along the edges until a vertex is repeated, and a simple cycle is formed. The winner is determined by some fixed property Y of the sequence of labels of the edges (or nodes) forming this cycle. These games are traditionally of interest because of their connection with infinite-duration games such as parity and mean-payoff games. We study the memory requirements for winning strategies of FCGs and certain associated infinite duration games. We exhibit a simple FCG that is not memoryless determined (this corrects a mistake in Memoryless determinacy of parity and mean payoff games: a simple proof by Bj⋯orklund, Sandberg, Vorobyov (2004) that claims that FCGs for which Y is closed under cyclic permutations are memoryless determined). We show that θ (n)! memory (where n is the number of nodes in the graph), which is always sufficient, may be necessary to win some FCGs. On the other hand, we identify easy to check conditions on Y (i.e., Y is closed under cyclic permutations, and both Y and its complement are closed under concatenation) that are sufficient to ensure that the corresponding FCGs and their associated infinite duration games are memoryless determined. We demonstrate that many games considered in the literature, such as mean-payoff, parity, energy, etc., satisfy these conditions. On the complexity side, we show (for efficiently computable Y) that while solving FCGs is in PSPACE, solving some families of FCGs is PSPACE-hard.

Planar matchings for weighted straight skeletons - Biedl, Therese; Huber, Stefan; Palfrader, Peter (25th International Symposium, ISAAC 2014)
In this paper, we introduce planar matchings on directed pseudo-line arrangements, which yield a planar set of pseudo-line segments such that only matching-partners are adjacent. By translating the planar matching problem into a corresponding stable roommates problem we show that such matchings always exist. Using our new framework, we establish, for the first time, a complete, rigorous definition of weighted straight skeletons, which are based on a so-called wavefront propagation process. We present a generalized and unified approach to treat structural changes in the wavefront that focuses on the restoration of weak planarity by finding planar matchings.

Fitness consequences of maternal and grandmaternal effects - Prizak, Roshan; Ezard, Thomas; Hoyle, Rebecca (Ecology and Evolution)
Transgenerational effects are broader than only parental relationships. Despite mounting evidence that multigenerational effects alter phenotypic and life-history traits, our understanding of how they combine to determine fitness is not well developed because of the added complexity necessary to study them. Here, we derive a quantitative genetic model of adaptation to an extraordinary new environment by an additive genetic component, phenotypic plasticity, maternal and grandmaternal effects. We show how, at equilibrium, negative maternal and negative grandmaternal effects maximize expected population mean fitness. We define negative transgenerational effects as those that have a negative effect on trait expression in the subsequent generation, that is, they slow, or potentially reverse, the expected evolutionary dynamic. When maternal effects are positive, negative grandmaternal effects are preferred. As expected under Mendelian inheritance, the grandmaternal effects have a lower impact on fitness than the maternal effects, but this dual inheritance model predicts a more complex relationship between maternal and grandmaternal effects to constrain phenotypic variance and so maximize expected population mean fitness in the offspring.

Partial-observation stochastic reachability and parity games - Chatterjee, Krishnendu
We consider two-player zero-sum partial-observation stochastic games on graphs. Based on the information available to the players these games can be classified as follows: (a) general partial-observation (both players have partial view of the game); (b) one-sided partial-observation (one player has partial-observation and the other player has complete-observation); and (c) perfect-observation (both players have complete view of the game). The one-sided partial-observation games subsumes the important special case of one-player partial-observation stochastic games (or partial-observation Markov decision processes (POMDPs)). Based on the randomization available for the strategies, (a) the players may not be allowed to use randomization (pure strategies), or (b) they may choose a probability distribution over actions but the actual random choice is external and not visible to the player (actions invisible), or (c) they may use full randomization. We consider all these classes of games with reachability, and parity objectives that can express all ω-regular objectives. The analysis problems are classified into the qualitative analysis that asks for the existence of a strategy that ensures the objective with probability 1; and the quantitative analysis that asks for the existence of a strategy that ensures the objective with probability at least λ (0,1). In this talk we will cover a wide range of results: for perfect-observation games; for POMDPs; for one-sided partial-observation games; and for general partial-observation games.

Partial-observation stochastic games: How to win when belief fails - Chatterjee, Krishnendu; Doyen, Laurent (ACM Transactions on Computational Logic (TOCL))
In two-player finite-state stochastic games of partial observation on graphs, in every state of the graph, the players simultaneously choose an action, and their joint actions determine a probability distribution over the successor states. The game is played for infinitely many rounds and thus the players construct an infinite path in the graph. We consider reachability objectives where the first player tries to ensure a target state to be visited almost-surely (i.e., with probability 1) or positively (i.e., with positive probability), no matter the strategy of the second player. We classify such games according to the information and to the power of randomization available to the players. On the basis of information, the game can be one-sided with either (a) player 1, or (b) player 2 having partial observation (and the other player has perfect observation), or two-sided with (c) both players having partial observation. On the basis of randomization, (a) the players may not be allowed to use randomization (pure strategies), or (b) they may choose a probability distribution over actions but the actual random choice is external and not visible to the player (actions invisible), or (c) they may use full randomization. Our main results for pure strategies are as follows: (1) For one-sided games with player 2 having perfect observation we show that (in contrast to full randomized strategies) belief-based (subset-construction based) strategies are not sufficient, and we present an exponential upper bound on memory both for almost-sure and positive winning strategies; we show that the problem of deciding the existence of almost-sure and positive winning strategies for player 1 is EXPTIME-complete and present symbolic algorithms that avoid the explicit exponential construction. (2) For one-sided games with player 1 having perfect observation we show that nonelementarymemory is both necessary and sufficient for both almost-sure and positive winning strategies. (3) We show that for the general (two-sided) case finite-memory strategies are sufficient for both positive and almost-sure winning, and at least nonelementary memory is required. We establish the equivalence of the almost-sure winning problems for pure strategies and for randomized strategies with actions invisible. Our equivalence result exhibit serious flaws in previous results of the literature: we show a nonelementary memory lower bound for almost-sure winning whereas an exponential upper bound was previously claimed.

Temporal specifications with accumulative values - Boker, Udi; Chatterjee, Krishnendu; Henzinger, Thomas A; Kupferman, Orna (ACM Transactions on Computational Logic (TOCL))
Recently, there has been an effort to add quantitative objectives to formal verification and synthesis. We introduce and investigate the extension of temporal logics with quantitative atomic assertions. At the heart of quantitative objectives lies the accumulation of values along a computation. It is often the accumulated sum, as with energy objectives, or the accumulated average, as with mean-payoff objectives. We investigate the extension of temporal logics with the prefix-accumulation assertions Sum(v) ≥ c and Avg(v) ≥ c, where v is a numeric (or Boolean) variable of the system, c is a constant rational number, and Sum(v) and Avg(v) denote the accumulated sum and average of the values of v from the beginning of the computation up to the current point in time. We also allow the path-accumulation assertions LimInfAvg(v) ≥ c and LimSupAvg(v) ≥ c, referring to the average value along an entire infinite computation. We study the border of decidability for such quantitative extensions of various temporal logics. In particular, we show that extending the fragment of CTL that has only the EX, EF, AX, and AG temporal modalities with both prefix-accumulation assertions, or extending LTL with both path-accumulation assertions, results in temporal logics whose model-checking problem is decidable. Moreover, the prefix-accumulation assertions may be generalized with "controlled accumulation," allowing, for example, to specify constraints on the average waiting time between a request and a grant. On the negative side, we show that this branching-time logic is, in a sense, the maximal logic with one or both of the prefix-accumulation assertions that permits a decidable model-checking procedure. Extending a temporal logic that has the EG or EU modalities, such as CTL or LTL, makes the problem undecidable.

The complexity of ergodic mean payoff games - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus
We study two-player (zero-sum) concurrent mean-payoff games played on a finite-state graph. We focus on the important sub-class of ergodic games where all states are visited infinitely often with probability 1. The algorithmic study of ergodic games was initiated in a seminal work of Hoffman and Karp in 1966, but all basic complexity questions have remained unresolved. Our main results for ergodic games are as follows: We establish (1) an optimal exponential bound on the patience of stationary strategies (where patience of a distribution is the inverse of the smallest positive probability and represents a complexity measure of a stationary strategy); (2) the approximation problem lies in FNP; (3) the approximation problem is at least as hard as the decision problem for simple stochastic games (for which NP ∩ coNP is the long-standing best known bound). We present a variant of the strategy-iteration algorithm by Hoffman and Karp; show that both our algorithm and the classical value-iteration algorithm can approximate the value in exponential time; and identify a subclass where the value-iteration algorithm is a FPTAS. We also show that the exact value can be expressed in the existential theory of the reals, and establish square-root sum hardness for a related class of games.

The complexity of partial-observation stochastic parity games with finite-memory strategies - Chatterjee, Krishnendu; Doyen, Laurent; Nain, Sumit; Vardi, Moshe
We consider two-player partial-observation stochastic games on finitestate graphs where player 1 has partial observation and player 2 has perfect observation. The winning condition we study are ε-regular conditions specified as parity objectives. The qualitative-analysis problem given a partial-observation stochastic game and a parity objective asks whether there is a strategy to ensure that the objective is satisfied with probability 1 (resp. positive probability). These qualitative-analysis problems are known to be undecidable. However in many applications the relevant question is the existence of finite-memory strategies, and the qualitative-analysis problems under finite-memory strategies was recently shown to be decidable in 2EXPTIME.We improve the complexity and show that the qualitative-analysis problems for partial-observation stochastic parity games under finite-memory strategies are EXPTIME-complete; and also establish optimal (exponential) memory bounds for finite-memory strategies required for qualitative analysis.

Perfect-information stochastic mean-payoff parity games - Chatterjee, Krishnendu; Doyen, Laurent; Gimbert, Hugo; Oualhadj, Youssouf
The theory of graph games is the foundation for modeling and synthesizing reactive processes. In the synthesis of stochastic processes, we use 2 1/2-player games where some transitions of the game graph are controlled by two adversarial players, the System and the Environment, and the other transitions are determined probabilistically. We consider 2 1/2-player games where the objective of the System is the conjunction of a qualitative objective (specified as a parity condition) and a quantitative objective (specified as a mean-payoff condition). We establish that the problem of deciding whether the System can ensure that the probability to satisfy the mean-payoff parity objective is at least a given threshold is in NP ∩ coNP, matching the best known bound in the special case of 2-player games (where all transitions are deterministic). We present an algorithm running in time O(d·n2d·MeanGame) to compute the set of almost-sure winning states from which the objective can be ensured with probability 1, where n is the number of states of the game, d the number of priorities of the parity objective, and MeanGame is the complexity to compute the set of almost-sure winning states in 2 1/2-player mean-payoff games. Our results are useful in the synthesis of stochastic reactive systems with both functional requirement (given as a qualitative objective) and performance requirement (given as a quantitative objective).

Edit distance for timed automata - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Majumdar, Ritankar
The edit distance between two (untimed) traces is the minimum cost of a sequence of edit operations (insertion, deletion, or substitution) needed to transform one trace to the other. Edit distances have been extensively studied in the untimed setting, and form the basis for approximate matching of sequences in different domains such as coding theory, parsing, and speech recognition. In this paper, we lift the study of edit distances from untimed languages to the timed setting. We define an edit distance between timed words which incorporates both the edit distance between the untimed words and the absolute difference in time stamps. Our edit distance between two timed words is computable in polynomial time. Further, we show that the edit distance between a timed word and a timed language generated by a timed automaton, defined as the edit distance between the word and the closest word in the language, is PSPACE-complete. While computing the edit distance between two timed automata is undecidable, we show that the approximate version, where we decide if the edit distance between two timed automata is either less than a given parameter or more than δ away from the parameter, for δ > 0, can be solved in exponential space and is EXPSPACE-hard. Our definitions and techniques can be generalized to the setting of hybrid systems, and analogous decidability results hold for rectangular automata.

Compositional specifications for IOCO testing - Daca, Przemyslaw; Henzinger, Thomas A; Krenn, Willibald; Nickovic, Dejan
Model-based testing is a promising technology for black-box software and hardware testing, in which test cases are generated automatically from high-level specifications. Nowadays, systems typically consist of multiple interacting components and, due to their complexity, testing presents a considerable portion of the effort and cost in the design process. Exploiting the compositional structure of system specifications can considerably reduce the effort in model-based testing. Moreover, inferring properties about the system from testing its individual components allows the designer to reduce the amount of integration testing. In this paper, we study compositional properties of the IOCO-testing theory. We propose a new approach to composition and hiding operations, inspired by contract-based design and interface theories. These operations preserve behaviors that are compatible under composition and hiding, and prune away incompatible ones. The resulting specification characterizes the input sequences for which the unit testing of components is sufficient to infer the correctness of component integration without the need for further tests. We provide a methodology that uses these results to minimize integration testing effort, but also to detect potential weaknesses in specifications. While we focus on asynchronous models and the IOCO conformance relation, the resulting methodology can be applied to a broader class of systems.

CEGAR for qualitative analysis of probabilistic systems - Chatterjee, Krishnendu; Daca, Przemyslaw; Chmelik, Martin
We consider Markov decision processes (MDPs) which are a standard model for probabilistic systems. We focus on qualitative properties for MDPs that can express that desired behaviors of the system arise almost-surely (with probability 1) or with positive probability. We introduce a new simulation relation to capture the refinement relation of MDPs with respect to qualitative properties, and present discrete graph theoretic algorithms with quadratic complexity to compute the simulation relation. We present an automated technique for assume-guarantee style reasoning for compositional analysis of MDPs with qualitative properties by giving a counter-example guided abstraction-refinement approach to compute our new simulation relation. We have implemented our algorithms and show that the compositional analysis leads to significant improvements.

CEGAR for qualitative analysis of probabilistic systems - Chatterjee, Krishnendu; Daca, Przemyslaw; Chmelik, Martin
We consider Markov decision processes (MDPs) which are a standard model for probabilistic systems. We focus on qualitative properties for MDPs that can express that desired behaviors of the system arise almost-surely (with probability 1) or with positive probability. We introduce a new simulation relation to capture the refinement relation of MDPs with respect to qualitative properties, and present discrete graph theoretic algorithms with quadratic complexity to compute the simulation relation. We present an automated technique for assume-guarantee style reasoning for compositional analysis of MDPs with qualitative properties by giving a counter-example guided abstraction-refinement approach to compute our new simulation relation. We have implemented our algorithms and show that the compositional analysis leads to significant improvements.

CEGAR for qualitative analysis of probabilistic systems - Chatterjee, Krishnendu; Daca, Przemyslaw; Chmelik, Martin
We consider Markov decision processes (MDPs) which are a standard model for probabilistic systems. We focus on qualitative properties for MDPs that can express that desired behaviors of the system arise almost-surely (with probability 1) or with positive probability. We introduce a new simulation relation to capture the refinement relation of MDPs with respect to qualitative properties, and present discrete graph theoretic algorithms with quadratic complexity to compute the simulation relation. We present an automated technique for assume-guarantee style reasoning for compositional analysis of MDPs with qualitative properties by giving a counter-example guided abstraction-refinement approach to compute our new simulation relation. We have implemented our algorithms and show that the compositional analysis leads to significant improvements.

Games with a weak adversary - Chatterjee, Krishnendu; Doyen, Laurent (Lecture Notes in Computer Science)
We consider multi-player graph games with partial-observation and parity objective. While the decision problem for three-player games with a coalition of the first and second players against the third player is undecidable in general, we present a decidability result for partial-observation games where the first and third player are in a coalition against the second player, thus where the second player is adversarial but weaker due to partial-observation. We establish tight complexity bounds in the case where player 1 is less informed than player 2, namely 2-EXPTIME-completeness for parity objectives. The symmetric case of player 1 more informed than player 2 is much more complicated, and we show that already in the case where player 1 has perfect observation, memory of size non-elementary is necessary in general for reachability objectives, and the problem is decidable for safety and reachability objectives. From our results we derive new complexity results for partial-observation stochastic games.

Improved algorithms for reachability and shortest path on low tree-width graphs - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Pavlogiannis, Andreas
We consider the reachability and shortest path problems on low tree-width graphs, with n nodes, m edges, and tree-width t, on a standard RAM with wordsize W. We use O to hide polynomial factors of the inverse of the Ackermann function. Our main contributions are three fold: 1. For reachability, we present an algorithm that requires O(n·t2·log(n/t)) preprocessing time, O(n·(t·log(n/t))/W) space, and O(t/W) time for pair queries and O((n·t)/W) time for single-source queries. Note that for constant t our algorithm uses O(n·logn) time for preprocessing; and O(n/W) time for single-source queries, which is faster than depth first search/breath first search (after the preprocessing). 2. We present an algorithm for shortest path that requires O(n·t2) preprocessing time, O(n·t) space, and O(t2) time for pair queries and O(n·t) time single-source queries. 3. We give a space versus query time trade-off algorithm for shortest path that, given any constant >0, requires O(n·t2) preprocessing time, O(n·t2) space, and O(n1−·t2) time for pair queries. Our algorithms improve all existing results, and use very simple data structures.

Model measuring for hybrid systems - Henzinger, Thomas A; Otop, Jan (Proceedings of the 17th international conference on Hybrid systems: computation and control)
As hybrid systems involve continuous behaviors, they should be evaluated by quantitative methods, rather than qualitative methods. In this paper we adapt a quantitative framework, called model measuring, to the hybrid systems domain. The model-measuring problem asks, given a model M and a specification, what is the maximal distance such that all models within that distance from M satisfy (or violate) the specification. A distance function on models is given as part of the input of the problem. Distances, especially related to continuous behaviors are more natural in the hybrid case than the discrete case. We are interested in distances represented by monotonic hybrid automata, a hybrid counterpart of (discrete) weighted automata, whose recognized timed languages are monotone (w.r.t. inclusion) in the values of parameters. The contributions of this paper are twofold. First, we give sufficient conditions under which the model-measuring problem can be solved. Second, we discuss the modeling of distances and applications of the model-measuring problem.

From model checking to model measuring - Henzinger, Thomas A; Otop, Jan
We define the model-measuring problem: given a model M and specification φ, what is the maximal distance ρ such that all models M'within distance ρ from M satisfy (or violate)φ. The model measuring problem presupposes a distance function on models. We concentrate on automatic distance functions, which are defined by weighted automata. The model-measuring problem subsumes several generalizations of the classical model-checking problem, in particular, quantitative model-checking problems that measure the degree of satisfaction of a specification, and robustness problems that measure how much a model can be perturbed without violating the specification. We show that for automatic distance functions, and ω-regular linear-time and branching-time specifications, the model-measuring problem can be solved. We use automata-theoretic model-checking methods for model measuring, replacing the emptiness question for standard word and tree automata by the optimal-weight question for the weighted versions of these automata. We consider weighted automata that accumulate weights by maximizing, summing, discounting, and limit averaging. We give several examples of using the model-measuring problem to compute various notions of robustness and quantitative satisfaction for temporal specifications.

Model measuring for hybrid systems - Henzinger, Thomas A; Otop, Jan
As hybrid systems involve continuous behaviors, they should be evaluated by quantitative methods, rather than qualitative methods. In this paper we adapt a quantitative framework, called model measuring, to the hybrid systems domain. The model-measuring problem asks, given a model M and a specification, what is the maximal distance such that all models within that distance from M satisfy (or violate) the specification. A distance function on models is given as part of the input of the problem. Distances, especially related to continuous behaviors are more natural in the hybrid case than the discrete case. We are interested in distances represented by monotonic hybrid automata, a hybrid counterpart of (discrete) weighted automata, whose recognized timed languages are monotone (w.r.t. inclusion) in the values of parameters.The contributions of this paper are twofold. First, we give sufficient conditions under which the model-measuring problem can be solved. Second, we discuss the modeling of distances and applications of the model-measuring problem.

Games with a weak adversary - Chatterjee, Krishnendu; Doyen, Laurent
We consider multi-player graph games with partial-observation and parity objective. While the decision problem for three-player games with a coalition of the first and second players against the third player is undecidable, we present a decidability result for partial-observation games where the first and third player are in a coalition against the second player, thus where the second player is adversarial but weaker due to partial-observation. We establish tight complexity bounds in the case where player 1 is less informed than player 2, namely 2-EXPTIME-completeness for parity objectives. The symmetric case of player 1 more informed than player 2 is much more complicated, and we show that already in the case where player 1 has perfect observation, memory of size non-elementary is necessary in general for reachability objectives, and the problem is decidable for safety and reachability objectives. Our results have tight connections with partial-observation stochastic games for which we derive new complexity results.

The value 1 problem for concurrent mean-payoff games - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus
We consider concurrent mean-payoff games, a very well-studied class of two-player (player 1 vs player 2) zero-sum games on finite-state graphs where every transition is assigned a reward between 0 and 1, and the payoff function is the long-run average of the rewards. The value is the maximal expected payoff that player 1 can guarantee against all strategies of player 2. We consider the computation of the set of states with value 1 under finite-memory strategies for player 1, and our main results for the problem are as follows: (1) we present a polynomial-time algorithm; (2) we show that whenever there is a finite-memory strategy, there is a stationary strategy that does not need memory at all; and (3) we present an optimal bound (which is double exponential) on the patience of stationary strategies (where patience of a distribution is the inverse of the smallest positive probability and represents a complexity measure of a stationary strategy).

Qualitative analysis of POMDPs with temporal logic specifications for robotics applications - Chatterjee, Krishnendu; Chmelik, Martin; Gupta, Raghav; Kanodia, Ayush
We consider partially observable Markov decision processes (POMDPs), that are a standard framework for robotics applications to model uncertainties present in the real world, with temporal logic specifications. All temporal logic specifications in linear-time temporal logic (LTL) can be expressed as parity objectives. We study the qualitative analysis problem for POMDPs with parity objectives that asks whether there is a controller (policy) to ensure that the objective holds with probability 1 (almost-surely). While the qualitative analysis of POMDPs with parity objectives is undecidable, recent results show that when restricted to finite-memory policies the problem is EXPTIME-complete. While the problem is intractable in theory, we present a practical approach to solve the qualitative analysis problem. We designed several heuristics to deal with the exponential complexity, and have used our implementation on a number of well-known POMDP examples for robotics applications. Our results provide the first practical approach to solve the qualitative analysis of robot motion planning with LTL properties in the presence of uncertainty.

Qualitative analysis of POMDPs with temporal logic specifications for robotics applications - Chatterjee, Krishnendu; Chmelik, Martin; Gupta, Raghav; Kanodia, Ayush
We consider partially observable Markov decision processes (POMDPs), that are a standard framework for robotics applications to model uncertainties present in the real world, with temporal logic specifications. All temporal logic specifications in linear-time temporal logic (LTL) can be expressed as parity objectives. We study the qualitative analysis problem for POMDPs with parity objectives that asks whether there is a controller (policy) to ensure that the objective holds with probability 1 (almost-surely). While the qualitative analysis of POMDPs with parity objectives is undecidable, recent results show that when restricted to finite-memory policies the problem is EXPTIME-complete. While the problem is intractable in theory, we present a practical approach to solve the qualitative analysis problem. We designed several heuristics to deal with the exponential complexity, and have used our implementation on a number of well-known POMDP examples for robotics applications. Our results provide the first practical approach to solve the qualitative analysis of robot motion planning with LTL properties in the presence of uncertainty.

A framework for automated competitive analysis of on-line scheduling of firm-deadline tasks - Chatterjee, Krishnendu; Kössler, Alexander; Pavlogiannis, Andreas; Schmid, Ulrich
We present a flexible framework for the automated competitive analysis of on-line scheduling algorithms for firm- deadline real-time tasks based on multi-objective graphs: Given a taskset and an on-line scheduling algorithm specified as a labeled transition system, along with some optional safety, liveness, and/or limit-average constraints for the adversary, we automatically compute the competitive ratio of the algorithm w.r.t. a clairvoyant scheduler. We demonstrate the flexibility and power of our approach by comparing the competitive ratio of several on-line algorithms, including D(over), that have been proposed in the past, for various tasksets. Our experimental results reveal that none of these algorithms is universally optimal, in the sense that there are tasksets where other schedulers provide better performance. Our framework is hence a very useful design tool for selecting optimal algorithms for a given application.

Optimal tree-decomposition balancing and reachability on low treewidth graphs - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Pavlogiannis, Andreas
We consider graphs with n nodes together with their tree-decomposition that has b = O ( n ) bags and width t , on the standard RAM computational model with wordsize W = Θ (log n ) . Our contributions are two-fold: Our first contribution is an algorithm that given a graph and its tree-decomposition as input, computes a binary and balanced tree-decomposition of width at most 4 · t + 3 of the graph in O ( b ) time and space, improving a long-standing (from 1992) bound of O ( n · log n ) time for constant treewidth graphs. Our second contribution is on reachability queries for low treewidth graphs. We build on our tree-balancing algorithm and present a data-structure for graph reachability that requires O ( n · t 2 ) preprocessing time, O ( n · t ) space, and O ( d t/ log n e ) time for pair queries, and O ( n · t · log t/ log n ) time for single-source queries. For constant t our data-structure uses O ( n ) time for preprocessing, O (1) time for pair queries, and O ( n/ log n ) time for single-source queries. This is (asymptotically) optimal and is faster than DFS/BFS when answering more than a constant number of single-source queries.

Nested weighted automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan
Recently there has been a significant effort to add quantitative properties in formal verification and synthesis. While weighted automata over finite and infinite words provide a natural and flexible framework to express quantitative properties, perhaps surprisingly, several basic system properties such as average response time cannot be expressed with weighted automata. In this work, we introduce nested weighted automata as a new formalism for expressing important quantitative properties such as average response time. We establish an almost complete decidability picture for the basic decision problems for nested weighted automata, and illustrate its applicability in several domains.

The complexity of evolution on graphs - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Nowak, Martin
Evolution occurs in populations of reproducing individuals. The structure of the population affects the outcome of the evolutionary process. Evolutionary graph theory is a powerful approach to study this phenomenon. There are two graphs. The interaction graph specifies who interacts with whom in the context of evolution. The replacement graph specifies who competes with whom for reproduction. The vertices of the two graphs are the same, and each vertex corresponds to an individual. A key quantity is the fixation probability of a new mutant. It is defined as the probability that a newly introduced mutant (on a single vertex) generates a lineage of offspring which eventually takes over the entire population of resident individuals. The basic computational questions are as follows: (i) the qualitative question asks whether the fixation probability is positive; and (ii) the quantitative approximation question asks for an approximation of the fixation probability. Our main results are: (1) We show that the qualitative question is NP-complete and the quantitative approximation question is #P-hard in the special case when the interaction and the replacement graphs coincide and even with the restriction that the resident individuals do not reproduce (which corresponds to an invading population taking over an empty structure). (2) We show that in general the qualitative question is PSPACE-complete and the quantitative approximation question is PSPACE-hard and can be solved in exponential time.

Doomsday equilibria for omega-regular games - Chatterjee, Krishnendu; Doyen, Laurent; Filiot, Emmanuel; Raskin, Jean-François (VMCAI 2014: Verification, Model Checking, and Abstract Interpretation)
Two-player games on graphs provide the theoretical framework for many important problems such as reactive synthesis. While the traditional study of two-player zero-sum games has been extended to multi-player games with several notions of equilibria, they are decidable only for perfect-information games, whereas several applications require imperfect-information games. In this paper we propose a new notion of equilibria, called doomsday equilibria, which is a strategy profile such that all players satisfy their own objective, and if any coalition of players deviates and violates even one of the players objective, then the objective of every player is violated. We present algorithms and complexity results for deciding the existence of doomsday equilibria for various classes of ω-regular objectives, both for imperfect-information games, and for perfect-information games.We provide optimal complexity bounds for imperfect-information games, and in most cases for perfect-information games.

A Short Course in Computational Geometry and Topology - Edelsbrunner, Herbert
This monograph presents a short course in computational geometry and topology. In the first part the book covers Voronoi diagrams and Delaunay triangulations, then it presents the theory of alpha complexes which play a crucial role in biology. The central part of the book is the homology theory and their computation, including the theory of persistence which is indispensable for applications, e.g. shape reconstruction. The target audience comprises researchers and practitioners in mathematics, biology, neuroscience and computer science, but the book may also be beneficial to graduate students of these fields.

Playful Math - An introduction to mathematical games - Huszár, Kristóf; Rolinek, Michal

DNA methylation as a system of plant genomic immunity - Kim, M. Yvonne; Zilberman, Daniel (Trends in Plant Science)
Transposons are selfish genetic sequences that can increase their copy number and inflict substantial damage on their hosts. To combat these genomic parasites, plants have evolved multiple pathways to identify and silence transposons by methylating their DNA. Plants have also evolved mechanisms to limit the collateral damage from the antitransposon machinery. In this review, we examine recent developments that have elucidated many of the molecular workings of these pathways. We also highlight the evidence that the methylation and demethylation pathways interact, indicating that plants have a highly sophisticated, integrated system of transposon defense that has an important role in the regulation of gene expression.

Role of sex and migration in adaptation to sink environments - Lagator, Mato; Morgan, Andrew; Neve, Paul; Colegrave, Nick (Evolution)
Understanding the effects of sex and migration on adaptation to novel environments remains a key problem in evolutionary biology. Using a single-cell alga Chlamydomonas reinhardtii, we investigated how sex and migration affected rates of evolutionary rescue in a sink environment, and subsequent changes in fitness following evolutionary rescue. We show that sex and migration affect both the rate of evolutionary rescue and subsequent adaptation. However, their combined effects change as the populations adapt to a sink habitat. Both sex and migration independently increased rates of evolutionary rescue, but the effect of sex on subsequent fitness improvements, following initial rescue, changed with migration, as sex was beneficial in the absence of migration but constraining adaptation when combined with migration. These results suggest that sex and migration are beneficial during the initial stages of adaptation, but can become detrimental as the population adapts to its environment.

Data from: Role of sex and migration in adaptation to sink environments - Lagator, Mato; Morgan, Andrew; Neve, Paul; Colegrave, Nick
Understanding the effects of sex and migration on adaptation to novel environments remains a key problem in evolutionary biology. Using a single-cell alga Chlamydomonas reinhardtii, we investigated how sex and migration affected rates of evolutionary rescue in a sink environment, and subsequent changes in fitness following evolutionary rescue. We show that sex and migration affect both the rate of evolutionary rescue and subsequent adaptation. However, their combined effects change as the populations adapt to a sink habitat. Both sex and migration independently increased rates of evolutionary rescue, but the effect of sex on subsequent fitness improvements, following initial rescue, changed with migration, as sex was beneficial in the absence of migration but constraining adaptation when combined with migration. These results suggest that sex and migration are beneficial during the initial stages of adaptation, but can become detrimental as the population adapts to its environment.

So near and yet so far: Harmonic radar reveals reduced homing ability of Nosema infected honeybees - Wolf, Stephan; Mcmahon, Dino; Lim, Ka; Pull, Christopher; Clark, Suzanne; Paxton, Robert; Osborne, Juliet (PLoS One)
Pathogens may gain a fitness advantage through manipulation of the behaviour of their hosts. Likewise, host behavioural changes can be a defence mechanism, counteracting the impact of pathogens on host fitness. We apply harmonic radar technology to characterize the impact of an emerging pathogen - Nosema ceranae (Microsporidia) - on honeybee (Apis mellifera) flight and orientation performance in the field. Honeybees are the most important commercial pollinators. Emerging diseases have been proposed to play a prominent role in colony decline, partly through sub-lethal behavioural manipulation of their hosts. We found that homing success was significantly reduced in diseased (65.8%) versus healthy foragers (92.5%). Although lost bees had significantly reduced continuous flight times and prolonged resting times, other flight characteristics and navigational abilities showed no significant difference between infected and non-infected bees. Our results suggest that infected bees express normal flight characteristics but are constrained in their homing ability, potentially compromising the colony by reducing its resource inputs, but also counteracting the intra-colony spread of infection. We provide the first high-resolution analysis of sub-lethal effects of an emerging disease on insect flight behaviour. The potential causes and the implications for both host and parasite are discussed.

Supporting information - Wolf, Stephan; Mcmahon, Dino; Lim, Ka; Pull, Christopher; Clark, Suzanne; Paxton, Robert; Osborne, Juliet
Detailed description of the experimental prodedures, data analyses and additional statistical analyses of the results.

Dnmt1-independent CG methylation contributes to nucleosome positioning in diverse eukaryotes - Huff, Jason T.; Zilberman, Daniel (Cell)
Dnmt1 epigenetically propagates symmetrical CG methylation in many eukaryotes. Their genomes are typically depleted of CG dinucleotides because of imperfect repair of deaminated methylcytosines. Here, we extensively survey diverse species lacking Dnmt1 and show that, surprisingly, symmetrical CG methylation is nonetheless frequently present and catalyzed by a different DNA methyltransferase family, Dnmt5. Numerous Dnmt5-containing organisms that diverged more than a billion years ago exhibit clustered methylation, specifically in nucleosome linkers. Clustered methylation occurs at unprecedented densities and directly disfavors nucleosomes, contributing to nucleosome positioning between clusters. Dense methylation is enabled by a regime of genomic sequence evolution that enriches CG dinucleotides and drives the highest CG frequencies known. Species with linker methylation have small, transcriptionally active nuclei that approach the physical limits of chromatin compaction. These features constitute a previously unappreciated genome architecture, in which dense methylation influences nucleosome positions, likely facilitating nuclear processes under extreme spatial constraints.

The AAA-ATPase molecular chaperone Cdc48/p97 disassembles sumoylated centromeres, decondenses heterochromatin, and activates ribosomal RNA genes - Mérai, Zsuzsanna; Chumak, Nina; García-Aguilar, Marcelina; Hsieh, Tzung-Fu; Nishimura, Toshiro; Schoft, Vera K.; Bindics, János; Ślusarz, Lucyna; Arnoux, Stéphanie; Opravil, Susanne; Mechtler, Karl; Zilberman, Daniel; et al. (Proceedings of the National Academy of Sciences)
Centromeres mediate chromosome segregation and are defined by the centromere-specific histone H3 variant (CenH3)/centromere protein A (CENP-A). Removal of CenH3 from centromeres is a general property of terminally differentiated cells, and the persistence of CenH3 increases the risk of diseases such as cancer. However, active mechanisms of centromere disassembly are unknown. Nondividing Arabidopsis pollen vegetative cells, which transport engulfed sperm by extended tip growth, undergo loss of CenH3; centromeric heterochromatin decondensation; and bulk activation of silent rRNA genes, accompanied by their translocation into the nucleolus. Here, we show that these processes are blocked by mutations in the evolutionarily conserved AAA-ATPase molecular chaperone, CDC48A, homologous to yeast Cdc48 and human p97 proteins, both of which are implicated in ubiquitin/small ubiquitin-like modifier (SUMO)-targeted protein degradation. We demonstrate that CDC48A physically associates with its heterodimeric cofactor UFD1-NPL4, known to bind ubiquitin and SUMO, as well as with SUMO1-modified CenH3 and mutations in NPL4 phenocopy cdc48a mutations. In WT vegetative cell nuclei, genetically unlinked ribosomal DNA (rDNA) loci are uniquely clustered together within the nucleolus and all major rRNA gene variants, including those rDNA variants silenced in leaves, are transcribed. In cdc48a mutant vegetative cell nuclei, however, these rDNA loci frequently colocalized with condensed centromeric heterochromatin at the external periphery of the nucleolus. Our results indicate that the CDC48ANPL4 complex actively removes sumoylated CenH3 from centromeres and disrupts centromeric heterochromatin to release bulk rRNA genes into the nucleolus for ribosome production, which fuels single nucleus-driven pollen tube growth and is essential for plant reproduction.

Boolean modelling reveals new regulatory connections between transcription factors orchestrating the development of the ventral spinal cord - Lovrics, Anna; Gao, Yu; Juhász, Bianka; Bock, István; Byrne, Helen; Dinnyés, András; Kovács, Krisztián (PLoS One)
We have assembled a network of cell-fate determining transcription factors that play a key role in the specification of the ventral neuronal subtypes of the spinal cord on the basis of published transcriptional interactions. Asynchronous Boolean modelling of the network was used to compare simulation results with reported experimental observations. Such comparison highlighted the need to include additional regulatory connections in order to obtain the fixed point attractors of the model associated with the five known progenitor cell types located in the ventral spinal cord. The revised gene regulatory network reproduced previously observed cell state switches between progenitor cells observed in knock-out animal models or in experiments where the transcription factors were overexpressed. Furthermore the network predicted the inhibition of Irx3 by Nkx2.2 and this prediction was tested experimentally. Our results provide evidence for the existence of an as yet undescribed inhibitory connection which could potentially have significance beyond the ventral spinal cord. The work presented in this paper demonstrates the strength of Boolean modelling for identifying gene regulatory networks.

Transition probability between TF expression states when Dbx2 inhibits Nkx2.2 - Lovrics, Anna; Gao, Yu; Juhász, Bianka; Bock, István; Byrne, Helen M.; Dinnyés, András; Kovács, Krisztián

The time scale of evolutionary innovation - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Adlam, Ben; Nowak, Martin (PLoS Computational Biology)
A fundamental question in biology is the following: what is the time scale that is needed for evolutionary innovations? There are many results that characterize single steps in terms of the fixation time of new mutants arising in populations of certain size and structure. But here we ask a different question, which is concerned with the much longer time scale of evolutionary trajectories: how long does it take for a population exploring a fitness landscape to find target sequences that encode new biological functions? Our key variable is the length, (Formula presented.) of the genetic sequence that undergoes adaptation. In computer science there is a crucial distinction between problems that require algorithms which take polynomial or exponential time. The latter are considered to be intractable. Here we develop a theoretical approach that allows us to estimate the time of evolution as function of (Formula presented.) We show that adaptation on many fitness landscapes takes time that is exponential in (Formula presented.) even if there are broad selection gradients and many targets uniformly distributed in sequence space. These negative results lead us to search for specific mechanisms that allow evolution to work on polynomial time scales. We study a regeneration process and show that it enables evolution to work in polynomial time.

Increased grooming after repeated brood care provides sanitary benefits in a clonal ant - Westhus, Claudia; Ugelvig, Line V; Tourdot, Edouard; Heinze, Jürgen; Doums, Claudie; Cremer, Sylvia (Behavioral Ecology and Sociobiology)
Repeated pathogen exposure is a common threat in colonies of social insects, posing selection pressures on colony members to respond with improved disease-defense performance. We here tested whether experience gained by repeated tending of low-level fungus-exposed (Metarhizium robertsii) larvae may alter the performance of sanitary brood care in the clonal ant, Platythyrea punctata. We trained ants individually over nine consecutive trials to either sham-treated or fungus-exposed larvae. We then compared the larval grooming behavior of naive and trained ants and measured how effectively they removed infectious fungal conidiospores from the fungus-exposed larvae. We found that the ants changed the duration of larval grooming in response to both, larval treatment and their level of experience: (1) sham-treated larvae received longer grooming than the fungus-exposed larvae and (2) trained ants performed less self-grooming but longer larval grooming than naive ants, which was true for both, ants trained to fungus-exposed and also to sham-treated larvae. Ants that groomed the fungus-exposed larvae for longer periods removed a higher number of fungal conidiospores from the surface of the fungus-exposed larvae. As experienced ants performed longer larval grooming, they were more effective in fungal removal, thus making them better caretakers under pathogen attack of the colony. By studying this clonal ant, we can thus conclude that even in the absence of genetic variation between colony members, differences in experience levels of brood care may affect performance of sanitary brood care in social insects.

Selection history and epistatic interactions impact dynamics of adaptation to novel environmental stresses - Lagator, Mato; Colegrave, Nick; Neve, Paul (Proceedings of the Royal Society of London Series B Biological Sciences)
In rapidly changing environments, selection history may impact the dynamics of adaptation. Mutations selected in one environment may result in pleiotropic fitness trade-offs in subsequent novel environments, slowing the rates of adaptation. Epistatic interactions between mutations selected in sequential stressful environments may slow or accelerate subsequent rates of adaptation, depending on the nature of that interaction. We explored the dynamics of adaptation during sequential exposure to herbicides with different modes of action in Chlamydomonas reinhardtii. Evolution of resistance to two of the herbicides was largely independent of selection history. For carbetamide, previous adaptation to other herbicide modes of action positively impacted the likelihood of adaptation to this herbicide. Furthermore, while adaptation to all individual herbicides was associated with pleiotropic fitness costs in stress-free environments, we observed that accumulation of resistance mechanisms was accompanied by a reduction in overall fitness costs. We suggest that antagonistic epistasis may be a driving mechanism that enables populations to more readily adapt in novel environments. These findings highlight the potential for sequences of xenobiotics to facilitate the rapid evolution of multiple-drug and -pesticide resistance, as well as the potential for epistatic interactions between adaptive mutations to facilitate evolutionary rescue in rapidly changing environments.

Data from: Anti-pathogen protection versus survival costs mediated by an ectosymbiont in an ant host - Konrad, Matthias; Grasse, Anna V; Tragust, Simon; Cremer, Sylvia
The fitness effects of symbionts on their hosts can be context-dependent, with usually benign symbionts causing detrimental effects when their hosts are stressed, or typically parasitic symbionts providing protection towards their hosts (e.g. against pathogen infection). Here, we studied the novel association between the invasive garden ant Lasius neglectus and its fungal ectosymbiont Laboulbenia formicarum for potential costs and benefits. We tested ants with different Laboulbenia levels for their survival and immunity under resource limitation and exposure to the obligate killing entomopathogen Metarhizium brunneum. While survival of L. neglectus workers under starvation was significantly decreased with increasing Laboulbenia levels, host survival under Metarhizium exposure increased with higher levels of the ectosymbiont, suggesting a symbiont-mediated anti-pathogen protection, which seems to be driven mechanistically by both improved sanitary behaviours and an upregulated immune system. Ants with high Laboulbenia levels showed significantly longer self-grooming and elevated expression of immune genes relevant for wound repair and antifungal responses (β-1,3-glucan binding protein, Prophenoloxidase), compared with ants carrying low Laboulbenia levels. This suggests that the ectosymbiont Laboulbenia formicarum weakens its ant host by either direct resource exploitation or the costs of an upregulated behavioural and immunological response, which, however, provides a prophylactic protection upon later exposure to pathogens.

Data from: Selection history and epistatic interactions impact dynamics of adaptation to novel environmental stresses - Lagator, Mato; Colegrave, Nick; Neve, Paul
In rapidly changing environments, selection history may impact the dynamics of adaptation. Mutations selected in one environment may result in pleiotropic fitness trade-offs in subsequent novel environments, slowing the rates of adaptation. Epistatic interactions between mutations selected in sequential stressful environments may slow or accelerate subsequent rates of adaptation, depending on the nature of that interaction. We explored the dynamics of adaptation during sequential exposure to herbicides with different modes of action in Chlamydomonas reinhardtii. Evolution of resistance to two of the herbicides was largely independent of selection history. For carbetamide, previous adaptation to other herbicide modes of action positively impacted the likelihood of adaptation to this herbicide. Furthermore, while adaptation to all individual herbicides was associated with pleiotropic fitness costs in stress-free environments, we observed that accumulation of resistance mechanisms was accompanied by a reduction in overall fitness costs. We suggest that antagonistic epistasis may be a driving mechanism that enables populations to more readily adapt in novel environments. These findings highlight the potential for sequences of xenobiotics to facilitate the rapid evolution of multiple-drug and -pesticide resistance, as well as the potential for epistatic interactions between adaptive mutations to facilitate evolutionary rescue in rapidly changing environments.

Detailed proofs for “The time scale of evolutionary innovation” - Chatterjee, Krishnendu; Pavlogiannis, Andreas; Adlam, Ben; Novak, Martin

Likelihood-based inference of population history from low-coverage de novo genome assemblies - Hearn, Jack; Stone, Graham; Bunnefeld, Lynsey; Nicholls, James; Barton, Nicholas H; Lohse, Konrad (Molecular Ecology)
Short-read sequencing technologies have in principle made it feasible to draw detailed inferences about the recent history of any organism. In practice, however, this remains challenging due to the difficulty of genome assembly in most organisms and the lack of statistical methods powerful enough to discriminate between recent, nonequilibrium histories. We address both the assembly and inference challenges. We develop a bioinformatic pipeline for generating outgroup-rooted alignments of orthologous sequence blocks from de novo low-coverage short-read data for a small number of genomes, and show how such sequence blocks can be used to fit explicit models of population divergence and admixture in a likelihood framework. To illustrate our approach, we reconstruct the Pleistocene history of an oak-feeding insect (the oak gallwasp Biorhiza pallida), which, in common with many other taxa, was restricted during Pleistocene ice ages to a longitudinal series of southern refugia spanning the Western Palaearctic. Our analysis of sequence blocks sampled from a single genome from each of three major glacial refugia reveals support for an unexpected history dominated by recent admixture. Despite the fact that 80% of the genome is affected by admixture during the last glacial cycle, we are able to infer the deeper divergence history of these populations. These inferences are robust to variation in block length, mutation model and the sampling location of individual genomes within refugia. This combination of de novo assembly and numerical likelihood calculation provides a powerful framework for estimating recent population history that can be applied to any organism without the need for prior genetic resources.

Data from: Pupal cocoons affect sanitary brood care and limit fungal infections in ant colonies - Tragust, Simon; Ugelvig, Line V; Chapuisat, Michel; Heinze, Jürgen; Cremer, Sylvia
Background: The brood of ants and other social insects is highly susceptible to pathogens, particularly those that penetrate the soft larval and pupal cuticle. We here test whether the presence of a pupal cocoon, which occurs in some ant species but not in others, affects the sanitary brood care and fungal infection patterns after exposure to the entomopathogenic fungus Metarhizium brunneum. We use a) a comparative approach analysing four species with either naked or cocooned pupae and b) a within-species analysis of a single ant species, in which both pupal types co-exist in the same colony. Results: We found that the presence of a cocoon did not compromise fungal pathogen detection by the ants and that species with cocooned pupae increased brood grooming after pathogen exposure. All tested ant species further removed brood from their nests, which was predominantly expressed towards larvae and naked pupae treated with the live fungal pathogen. In contrast, cocooned pupae exposed to live fungus were not removed at higher rates than cocooned pupae exposed to dead fungus or a sham control. Consistent with this, exposure to the live fungus caused high numbers of infections and fungal outgrowth in larvae and naked pupae, but not in cocooned pupae. Moreover, the ants consistently removed the brood prior to fungal outgrowth, ensuring a clean brood chamber. Conclusion: Our study suggests that the pupal cocoon has a protective effect against fungal infection, causing an adaptive change in sanitary behaviours by the ants. It further demonstrates that brood removal - originally described for honeybees as “hygienic behaviour” – is a widespread sanitary behaviour in ants, which likely has important implications on disease dynamics in social insect colonies.

Data from: Transformation of stimulus correlations by the retina - Simmons, Kristina; Prentice, Jason; Tkačik, Gašper; Homann, Jan; Yee, Heather; Palmer, Stephanie; Nelson, Philip; Balasubramanian, Vijay
Redundancies and correlations in the responses of sensory neurons may seem to waste neural resources, but they can also carry cues about structured stimuli and may help the brain to correct for response errors. To investigate the effect of stimulus structure on redundancy in retina, we measured simultaneous responses from populations of retinal ganglion cells presented with natural and artificial stimuli that varied greatly in correlation structure; these stimuli and recordings are publicly available online. Responding to spatio-temporally structured stimuli such as natural movies, pairs of ganglion cells were modestly more correlated than in response to white noise checkerboards, but they were much less correlated than predicted by a non-adapting functional model of retinal response. Meanwhile, responding to stimuli with purely spatial correlations, pairs of ganglion cells showed increased correlations consistent with a static, non-adapting receptive field and nonlinearity. We found that in response to spatio-temporally correlated stimuli, ganglion cells had faster temporal kernels and tended to have stronger surrounds. These properties of individual cells, along with gain changes that opposed changes in effective contrast at the ganglion cell input, largely explained the pattern of pairwise correlations across stimuli where receptive field measurements were possible.

Increased gene dosage plays a predominant role in the initial stages of evolution of duplicate TEM-1 beta lactamase genes - Dhar, Riddhiman; Bergmiller, Tobias; Wagner, Andreas (Evolution)
Gene duplication is important in evolution, because it provides new raw material for evolutionary adaptations. Several existing hypotheses about the causes of duplicate retention and diversification differ in their emphasis on gene dosage, subfunctionalization, and neofunctionalization. Little experimental data exist on the relative importance of gene expression changes and changes in coding regions for the evolution of duplicate genes. Furthermore, we do not know how strongly the environment could affect this importance. To address these questions, we performed evolution experiments with the TEM-1 beta lactamase gene in Escherichia coli to study the initial stages of duplicate gene evolution in the laboratory. We mimicked tandem duplication by inserting two copies of the TEM-1 gene on the same plasmid. We then subjected these copies to repeated cycles of mutagenesis and selection in various environments that contained antibiotics in different combinations and concentrations. Our experiments showed that gene dosage is the most important factor in the initial stages of duplicate gene evolution, and overshadows the importance of point mutations in the coding region.

Data from: Increased gene dosage plays a predominant role in the initial stages of evolution of duplicate TEM-1 beta lactamase genes - Dhar, Riddhiman; Bergmiller, Tobias; Wagner, Andreas
Gene duplication is important in evolution, because it provides new raw material for evolutionary adaptations. Several existing hypotheses about the causes of duplicate retention and diversification differ in their emphasis on gene dosage, sub-functionalization, and neo-functionalization. Little experimental data exists on the relative importance of gene expression changes and changes in coding regions for the evolution of duplicate genes. Furthermore, we do not know how strongly the environment could affect this importance. To address these questions, we performed evolution experiments with the TEM-1 beta lactamase gene in E. coli to study the initial stages of duplicate gene evolution in the laboratory. We mimicked tandem duplication by inserting two copies of the TEM-1 gene on the same plasmid. We then subjected these copies to repeated cycles of mutagenesis and selection in various environments that contained antibiotics in different combinations and concentrations. Our experiments showed that gene dosage is the most important factor in the initial stages of duplicate gene evolution, and overshadows the importance of point mutations in the coding region.

Polynomial-time algorithms for energy games with special weight structures - Chatterjee, Krishnendu; Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon (Algorithmica)
Energy games belong to a class of turn-based two-player infinite-duration games played on a weighted directed graph. It is one of the rare and intriguing combinatorial problems that lie in NP∩co-NP, but are not known to be in P. The existence of polynomial-time algorithms has been a major open problem for decades and apart from pseudopolynomial algorithms there is no algorithm that solves any non-trivial subclass in polynomial time. In this paper, we give several results based on the weight structures of the graph. First, we identify a notion of penalty and present a polynomial-time algorithm when the penalty is large. Our algorithm is the first polynomial-time algorithm on a large class of weighted graphs. It includes several worst-case instances on which previous algorithms, such as value iteration and random facet algorithms, require at least sub-exponential time. Our main technique is developing the first non-trivial approximation algorithm and showing how to convert it to an exact algorithm. Moreover, we show that in a practical case in verification where weights are clustered around a constant number of values, the energy game problem can be solved in polynomial time. We also show that the problem is still as hard as in general when the clique-width is bounded or the graph is strongly ergodic, suggesting that restricting the graph structure does not necessarily help.

Visualization of two-dimensional symmetric positive definite tensor fields using the heat kernel signature - Zobel, Valentin; Reininghaus, Jan; Hotz, Ingrid (Topological Methods in Data Analysis and Visualization III)
We propose a method for visualizing two-dimensional symmetric positive definite tensor fields using the Heat Kernel Signature (HKS). The HKS is derived from the heat kernel and was originally introduced as an isometry invariant shape signature. Each positive definite tensor field defines a Riemannian manifold by considering the tensor field as a Riemannian metric. On this Riemmanian manifold we can apply the definition of the HKS. The resulting scalar quantity is used for the visualization of tensor fields. The HKS is closely related to the Gaussian curvature of the Riemannian manifold and the time parameter of the heat kernel allows a multiscale analysis in a natural way. In this way, the HKS represents field related scale space properties, enabling a level of detail analysis of tensor fields. This makes the HKS an interesting new scalar quantity for tensor fields, which differs significantly from usual tensor invariants like the trace or the determinant. A method for visualization and a numerical realization of the HKS for tensor fields is proposed in this chapter. To validate the approach we apply it to some illustrating simple examples as isolated critical points and to a medical diffusion tensor data set.

UV laser ablation to measure cell and tissue-generated forces in the zebrafish embryo in vivo and ex vivo - Smutny, Michael; Behrndt, Martin; Campinho, Pedro; Ruprecht, Verena; Heisenberg, Carl-Philipp J (Tissue Morphogenesis)
Mechanically coupled cells can generate forces driving cell and tissue morphogenesis during development. Visualization and measuring of these forces is of major importance to better understand the complexity of the biomechanic processes that shape cells and tissues. Here, we describe how UV laser ablation can be utilized to quantitatively assess mechanical tension in different tissues of the developing zebrafish and in cultures of primary germ layer progenitor cells ex vivo.

The excitation spectrum for Bose fluids with weak interactions - Seiringer, Robert (Jahresbericht der Deutschen Mathematiker-Vereinigung)
We review recent progress towards a rigorous understanding of the excitation spectrum of bosonic quantum many-body systems. In particular, we explain how one can rigorously establish the predictions resulting from the Bogoliubov approximation in the mean field limit. The latter predicts that the spectrum is made up of elementary excitations, whose energy behaves linearly in the momentum for small momentum. This property is crucial for the superfluid behavior of the system. We also discuss a list of open problems in this field.
Keywords: General Medicine

Notes on the simplification of the Morse-Smale complex - Günther, David; Reininghaus, Jan; Seidel, Hans-Peter; Weinkauf, Tino (Topological Methods in Data Analysis and Visualization III.)
The Morse-Smale complex can be either explicitly or implicitly represented. Depending on the type of representation, the simplification of the Morse-Smale complex works differently. In the explicit representation, the Morse-Smale complex is directly simplified by explicitly reconnecting the critical points during the simplification. In the implicit representation, on the other hand, the Morse-Smale complex is given by a combinatorial gradient field. In this setting, the simplification changes the combinatorial flow, which yields an indirect simplification of the Morse-Smale complex. The topological complexity of the Morse-Smale complex is reduced in both representations. However, the simplifications generally yield different results. In this chapter, we emphasize properties of the two representations that cause these differences. We also provide a complexity analysis of the two schemes with respect to running time and memory consumption.

Immune defences in ants: Effects of social immunisation and a fungal ectosymbiont in the ant Lasius neglectus - Konrad, Matthias
In this thesis I studied various individual and social immune defences employed by the invasive garden ant Lasius neglectus mostly against entomopathogenic fungi. The first two chapters of this thesis address the phenomenon of 'social immunisation'. Social immunisation, that is the immunological protection of group members due to social contact to a pathogen-exposed nestmate, has been described in various social insect species against different types of pathogens. However, in the case of entomopathogenic fungi it has, so far, only been demonstrated that social immunisation exists at all. Its underlying mechanisms r any other properties were, however, unknown. In the first chapter of this thesis I identified the mechanistic basis of social immunisation in L. neglectus against the entomopathogenous fungus Metarhizium. I could show that nestmates of a pathogen-exposed individual contract low-level infections due to social interactions. These low-level infections are, however, non-lethal and cause an active stimulation of the immune system, which protects the nestmates upon subsequent pathogen encounters. In the second chapter of this thesis I investigated the specificity and colony level effects of social immunisation. I demonstrated that the protection conferred by social immunisation is highly specific, protecting ants only against the same pathogen strain. In addition, depending on the respective context, social immunisation may even cause fitness costs. I further showed that social immunisation crucially affects sanitary behaviour and disease dynamics within ant groups. In the third chapter of this thesis I studied the effects of the ectosymbiotic fungus Laboulbenia formicarum on its host L. neglectus. Although Laboulbeniales are the largest order of insect-parasitic fungi, research concerning host fitness consequence is sparse. I showed that highly Laboulbenia-infected ants sustain fitness costs under resource limitation, however, gain fitness benefits when exposed to an entomopathogenus fungus. These effects are probably cause by a prophylactic upregulation of behavioural as well as physiological immune defences in highly infected ants.

Molecular mechanisms of patterning and subcellular trafficking in Arabidopsis thaliana - Marhavá, Petra
Phosphatidylinositol (Ptdlns) is a structural phospholipid that can be phosphorylated into various lipid signaling molecules, designated polyphosphoinositides (PPIs). The reversible phosphorylation of PPIs on the 3, 4, or 5 position of inositol is performed by a set of organelle-specific kinases and phosphatases, and the characteristic head groups make these molecules ideal for regulating biological processes in time and space. In yeast and mammals, Ptdlns3P and Ptdlns(3,5)P2 play crucial roles in trafficking toward the lytic compartments, whereas the role in plants is not yet fully understood. Here we identified the role of a land plant-specific subgroup of PPI phosphatases, the suppressor of actin 2 (SAC2) to SAC5, during vauolar trafficking and morphogenesis in Arabidopsis thaliana. SAC2-SAC5 localize to the tonoplast along with Ptdlns3P, the presumable product of their activity. in SAC gain- and loss-of-function mutants, the levels of Ptdlns monophosphates and bisphosphates were changed, with opposite effects on the morphology of storage and lytic vacuoles, and the trafficking toward the vacuoles was defective. Moreover, multiple sac knockout mutants had an increased number of smaller storage and lytic vacuoles, whereas extralarge vacuoles were observed in the overexpression lines, correlating with various growth and developmental defects. The fragmented vacuolar phenotype of sac mutants could be mimicked by treating wild-type seedlings with Ptdlns(3,5)P2, corroborating that this PPI is important for vacuole morphology. Taken together, these results provide evidence that PPIs, together with their metabolic enzymes SAC2-SAC5, are crucial for vacuolar trafficking and for vacuolar morphology and function in plants.

Stable length estimates of tube-like shapes - Edelsbrunner, Herbert; Pausinger, Florian (Journal of Mathematical Imaging and Vision)
Motivated by applications in biology, we present an algorithm for estimating the length of tube-like shapes in 3-dimensional Euclidean space. In a first step, we combine the tube formula of Weyl with integral geometric methods to obtain an integral representation of the length, which we approximate using a variant of the Koksma-Hlawka Theorem. In a second step, we use tools from computational topology to decrease the dependence on small perturbations of the shape. We present computational experiments that shed light on the stability and the convergence rate of our algorithm.

Eliminating Tverberg points, I. An analogue of the Whitney trick - Mabillard, Isaac; Wagner, Uli (Proceedings of the Annual Symposium on Computational Geometry)
Motivated by topological Tverberg-type problems, we consider multiple (double, triple, and higher multiplicity) selfintersection points of maps from finite simplicial complexes (compact polyhedra) into ℝd and study conditions under which such multiple points can be eliminated. The most classical case is that of embeddings (i.e., maps without double points) of a κ-dimensional complex K into ℝ2κ. For this problem, the work of van Kampen, Shapiro, and Wu provides an efficiently testable necessary condition for embeddability (namely, vanishing of the van Kampen ob-struction). For κ ≥ 3, the condition is also sufficient, and yields a polynomial-time algorithm for deciding embeddability: One starts with an arbitrary map f : K→ℝ2κ, which generically has finitely many double points; if k ≥ 3 and if the obstruction vanishes then one can successively remove these double points by local modifications of the map f. One of the main tools is the famous Whitney trick that permits eliminating pairs of double points of opposite intersection sign. We are interested in generalizing this approach to intersection points of higher multiplicity. We call a point y 2 ℝd an r-fold Tverberg point of a map f : Kκ →ℝd if y lies in the intersection f(σ1)∩. ∩f(σr) of the images of r pairwise disjoint simplices of K. The analogue of (non-)embeddability that we study is the problem Tverbergκ r→d: Given a κ-dimensional complex K, does it satisfy a Tverberg-type theorem with parameters r and d, i.e., does every map f : K κ → ℝd have an r-fold Tverberg point? Here, we show that for fixed r, κ and d of the form d = rm and k = (r-1)m, m ≥ 3, there is a polynomial-time algorithm for deciding this (based on the vanishing of a cohomological obstruction, as in the case of embeddings). Our main tool is an r-fold analogue of the Whitney trick: Given r pairwise disjoint simplices of K such that the intersection of their images contains two r-fold Tverberg points y+ and y- of opposite intersection sign, we can eliminate y+ and y- by a local isotopy of f. In a subsequent paper, we plan to develop this further and present a generalization of the classical Haeiger-Weber Theorem (which yields a necessary and sufficient condition for embeddability of κ-complexes into ℝd for a wider range of dimensions) to intersection points of higher multiplicity.

Habitat heterogeneities versus spatial type frequency variances as driving forces of dispersal evolution - Novak, Sebastian (Ecology and Evolution)
Understanding the evolution of dispersal is essential for understanding and predicting the dynamics of natural populations. Two main factors are known to influence dispersal evolution: spatio-temporal variation in the environment and relatedness between individuals. However, the relation between these factors is still poorly understood, and they are usually treated separately. In this article, I present a theoretical framework that contains and connects effects of both environmental variation and relatedness, and reproduces and extends their known features. Spatial habitat variation selects for balanced dispersal strategies, whereby the population is kept at an ideal free distribution. Within this class of dispersal strategies, I explain how increased dispersal is promoted by perturbations to the dispersal type frequencies. An explicit formula shows the magnitude of the selective advantage of increased dispersal in terms of the spatial variability in the frequencies of the different dispersal strategies present. These variances are capable of capturing various sources of stochasticity and hence establish a common scale for their effects on the evolution of dispersal. The results furthermore indicate an alternative approach to identifying effects of relatedness on dispersal evolution.

Regression-free synthesis for concurrency - Cerny, Pavol; Henzinger, Thomas A; Radhakrishna, Arjun; Ryzhyk, Leonid; Tarrach, Thorsten
While fixing concurrency bugs, program repair algorithms may introduce new concurrency bugs. We present an algorithm that avoids such regressions. The solution space is given by a set of program transformations we consider in the repair process. These include reordering of instructions within a thread and inserting atomic sections. The new algorithm learns a constraint on the space of candidate solutions, from both positive examples (error-free traces) and counterexamples (error traces). From each counterexample, the algorithm learns a constraint necessary to remove the errors. From each positive examples, it learns a constraint that is necessary in order to prevent the repair from turning the trace into an error trace. We implemented the algorithm and evaluated it on simplified Linux device drivers with known bugs.

Compositional specifications for IOCO testing - Daca, Przemyslaw; Henzinger, Thomas A; Krenn, Willibald; Nickovic, Dejan (IEEE 7th International Conference on Software Testing, Verification and Validation)
Model-based testing is a promising technology for black-box software and hardware testing, in which test cases are generated automatically from high-level specifications. Nowadays, systems typically consist of multiple interacting components and, due to their complexity, testing presents a considerable portion of the effort and cost in the design process. Exploiting the compositional structure of system specifications can considerably reduce the effort in model-based testing. Moreover, inferring properties about the system from testing its individual components allows the designer to reduce the amount of integration testing. In this paper, we study compositional properties of the ioco-testing theory. We propose a new approach to composition and hiding operations, inspired by contract-based design and interface theories. These operations preserve behaviors that are compatible under composition and hiding, and prune away incompatible ones. The resulting specification characterizes the input sequences for which the unit testing of components is sufficient to infer the correctness of component integration without the need for further tests. We provide a methodology that uses these results to minimize integration testing effort, but also to detect potential weaknesses in specifications. While we focus on asynchronous models and the ioco conformance relation, the resulting methodology can be applied to a broader class of systems.

CEGAR for qualitative analysis of probabilistic systems - Chatterjee, Krishnendu; Chmelik, Martin; Daca, Przemyslaw
We consider Markov decision processes (MDPs) which are a standard model for probabilistic systems.We focus on qualitative properties forMDPs that can express that desired behaviors of the system arise almost-surely (with probability 1) or with positive probability. We introduce a new simulation relation to capture the refinement relation ofMDPs with respect to qualitative properties, and present discrete graph theoretic algorithms with quadratic complexity to compute the simulation relation.We present an automated technique for assume-guarantee style reasoning for compositional analysis ofMDPs with qualitative properties by giving a counterexample guided abstraction-refinement approach to compute our new simulation relation. We have implemented our algorithms and show that the compositional analysis leads to significant improvements.

Bacterial responses to antibiotics and their combinations - Mitosch, Karin; Bollenbach, Tobias (Environmental Microbiology Reports)
Antibiotics affect bacterial cell physiology at many levels. Rather than just compensating for the direct cellular defects caused by the drug, bacteria respond to antibiotics by changing their morphology, macromolecular composition, metabolism, gene expression and possibly even their mutation rate. Inevitably, these processes affect each other, resulting in a complex response with changes in the expression of numerous genes. Genome‐wide approaches can thus help in gaining a comprehensive understanding of bacterial responses to antibiotics. In addition, a combination of experimental and theoretical approaches is needed for identifying general principles that underlie these responses. Here, we review recent progress in our understanding of bacterial responses to antibiotics and their combinations, focusing on effects at the levels of growth rate and gene expression. We concentrate on studies performed in controlled laboratory conditions, which combine promising experimental techniques with quantitative data analysis and mathematical modeling. While these basic research approaches are not immediately applicable in the clinic, uncovering the principles and mechanisms underlying bacterial responses to antibiotics may, in the long term, contribute to the development of new treatment strategies to cope with and prevent the rise of resistant pathogenic bacteria.

The exact PRF-security of NMAC and HMAC - Gazi, Peter; Pietrzak, Krzysztof Z; Rybar, Michal
NMAC is a mode of operation which turns a fixed input-length keyed hash function f into a variable input-length function. A practical single-key variant of NMAC called HMAC is a very popular and widely deployed message authentication code (MAC). Security proofs and attacks for NMAC can typically be lifted to HMAC. NMAC was introduced by Bellare, Canetti and Krawczyk [Crypto'96], who proved it to be a secure pseudorandom function (PRF), and thus also a MAC, assuming that (1) f is a PRF and (2) the function we get when cascading f is weakly collision-resistant. Unfortunately, HMAC is typically instantiated with cryptographic hash functions like MD5 or SHA-1 for which (2) has been found to be wrong. To restore the provable guarantees for NMAC, Bellare [Crypto'06] showed its security based solely on the assumption that f is a PRF, albeit via a non-uniform reduction. - Our first contribution is a simpler and uniform proof for this fact: If f is an ε-secure PRF (against q queries) and a δ-non-adaptively secure PRF (against q queries), then NMAC f is an (ε+ℓqδ)-secure PRF against q queries of length at most ℓ blocks each. - We then show that this ε+ℓqδ bound is basically tight. For the most interesting case where ℓqδ ≥ ε we prove this by constructing an f for which an attack with advantage ℓqδ exists. This also violates the bound O(ℓε) on the PRF-security of NMAC recently claimed by Koblitz and Menezes. - Finally, we analyze the PRF-security of a modification of NMAC called NI [An and Bellare, Crypto'99] that differs mainly by using a compression function with an additional keying input. This avoids the constant rekeying on multi-block messages in NMAC and allows for a security proof starting by the standard switch from a PRF to a random function, followed by an information-theoretic analysis. We carry out such an analysis, obtaining a tight ℓq2/2 c bound for this step, improving over the trivial bound of ℓ2q2/2c. The proof borrows combinatorial techniques originally developed for proving the security of CBC-MAC [Bellare et al., Crypto'05].

The notochord breaks bilateral symmetry by controlling cell shapes in the Zebrafish laterality organ - Compagnon, Julien; Barone, Vanessa; Rajshekar, Srivarsha; Kottmeier, Rita; Pranjic-Ferscha, Kornelija; Behrndt, Martin; Heisenberg, Carl-Philipp J (Developmental Cell)
Kupffer's vesicle (KV) is the zebrafish organ of laterality, patterning the embryo along its left-right (LR) axis. Regional differences in cell shape within the lumen-lining KV epithelium are essential for its LR patterning function. However, the processes by which KV cells acquire their characteristic shapes are largely unknown. Here, we show that the notochord induces regional differences in cell shape within KV by triggering extracellular matrix (ECM) accumulation adjacent to anterior-dorsal (AD) regions of KV. This localized ECM deposition restricts apical expansion of lumen-lining epithelial cells in AD regions of KV during lumen growth. Our study provides mechanistic insight into the processes by which KV translates global embryonic patterning into regional cell shape differences required for its LR symmetry-breaking function.

Spatio-temporally precise activation of engineered receptor tyrosine kinases by light - Grusch, Michael; Schelch, Karin; Riedler, Robert; Gschaider-Reichhart, Eva; Differ, Christopher; Berger, Walter; Inglés Prieto, Álvaro; Janovjak, Harald L (EMBO Journal)
Receptor tyrosine kinases (RTKs) are a large family of cell surface receptors that sense growth factors and hormones and regulate a variety of cell behaviours in health and disease. Contactless activation of RTKs with spatial and temporal precision is currently not feasible. Here, we generated RTKs that are insensitive to endogenous ligands but can be selectively activated by low-intensity blue light. We screened light-oxygen-voltage (LOV)-sensing domains for their ability to activate RTKs by light-activated dimerization. Incorporation of LOV domains found in aureochrome photoreceptors of stramenopiles resulted in robust activation of the fibroblast growth factor receptor 1 (FGFR1), epidermal growth factor receptor (EGFR) and rearranged during transfection (RET). In human cancer and endothelial cells, light induced cellular signalling with spatial and temporal precision. Furthermore, light faithfully mimicked complex mitogenic and morphogenic cell behaviour induced by growth factors. RTKs under optical control (Opto-RTKs) provide a powerful optogenetic approach to actuate cellular signals and manipulate cell behaviour.

Embeddability in the 3 sphere is decidable - Matoušek, Jiří; Sedgwick, Eric; Tancer, Martin; Wagner, Uli (Proceedings of the Annual Symposium on Computational Geometry)
We show that the following algorithmic problem is decidable: given a 2-dimensional simplicial complex, can it be embedded (topologically, or equivalently, piecewise linearly) in ℝ3? By a known reduction, it suffices to decide the embeddability of a given triangulated 3-manifold X into the 3-sphere S3. The main step, which allows us to simplify X and recurse, is in proving that if X can be embedded in S3, then there is also an embedding in which X has a short meridian, i.e., an essential curve in the boundary of X bounding a disk in S3 nX with length bounded by a computable function of the number of tetrahedra of X.

PHAT – Persistent Homology Algorithms Toolbox - Bauer, Ulrich; Kerber, Michael; Reininghaus, Jan; Wagner, Hubert (ICMS 2014: International Congress on Mathematical Software)
PHAT is a C++ library for the computation of persistent homology by matrix reduction. We aim for a simple generic design that decouples algorithms from data structures without sacrificing efficiency or user-friendliness. This makes PHAT a versatile platform for experimenting with algorithmic ideas and comparing them to state of the art implementations.

Quantitative fair simulation games - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan; Velner, Yaron
Simulation is an attractive alternative for language inclusion for automata as it is an under-approximation of language inclusion, but usually has much lower complexity. For non-deterministic automata, while language inclusion is PSPACE-complete, simulation can be computed in polynomial time. Simulation has also been extended in two orthogonal directions, namely, (1) fair simulation, for simulation over specified set of infinite runs; and (2) quantitative simulation, for simulation between weighted automata. Again, while fair trace inclusion is PSPACE-complete, fair simulation can be computed in polynomial time. For weighted automata, the (quantitative) language inclusion problem is undecidable for mean-payoff automata and the decidability is open for discounted-sum automata, whereas the (quantitative) simulation reduce to mean-payoff games and discounted-sum games, which admit pseudo-polynomial time algorithms. In this work, we study (quantitative) simulation for weighted automata with Büchi acceptance conditions, i.e., we generalize fair simulation from non-weighted automata to weighted automata. We show that imposing Büchi acceptance conditions on weighted automata changes many fundamental properties of the simulation games. For example, whereas for mean-payoff and discounted-sum games, the players do not need memory to play optimally; we show in contrast that for simulation games with Büchi acceptance conditions, (i) for mean-payoff objectives, optimal strategies for both players require infinite memory in general, and (ii) for discounted-sum objectives, optimal strategies need not exist for both players. While the simulation games with Büchi acceptance conditions are more complicated (e.g., due to infinite-memory requirements for mean-payoff objectives) as compared to their counterpart without Büchi acceptance conditions, we still present pseudo-polynomial time algorithms to solve simulation games with Büchi acceptance conditions for both weighted mean-payoff and weighted discounted-sum automata.

Gemeinsame Krankheitsabwehr in Ameisengesellschaften - Cremer, Sylvia (Zoologie)

Monitoring neurogenesis in the cerebral cortex: an update - Postiglione, Maria P; Hippenmeyer, Simon (Future Neurology)
The cerebral cortex, the seat of our cognitive abilities, is composed of an intricate network of billions of excitatory projection and inhibitory interneurons. Postmitotic cortical neurons are generated by a diverse set of neural stem cell progenitors within dedicated zones and defined periods of neurogenesis during embryonic development. Disruptions in neurogenesis can lead to alterations in the neuronal cytoarchitecture, which is thought to represent a major underlying cause for several neurological disorders, including microcephaly, autism and epilepsy. Although a number of signaling pathways regulating neurogenesis have been described, the precise cellular and molecular mechanisms regulating the functional neural stem cell properties in cortical neurogenesis remain unclear. Here, we discuss the most up-to-date strategies to monitor the fundamental mechanistic parameters of neuronal progenitor proliferation, and recent advances deciphering the logic and dynamics of neurogenesis.

Patterns of hippocampal tau pathology differentiate neurodegenerative dementias - Milenković, Ivan; Petrov, Tatjana; Kovács, Gábor (Dementia and Geriatric Cognitive Disorders)
Deposits of phosphorylated tau protein and convergence of pathology in the hippocampus are the hallmarks of neurodegenerative tauopathies. Thus we aimed to evaluate whether regional and cellular vulnerability patterns in the hippocampus distinguish tauopathies or are influenced by their concomitant presence. Methods: We created a heat map of phospho-tau (AT8) immunoreactivity patterns in 24 hippocampal subregions/layers in individuals with Alzheimer's disease (AD)-related neurofibrillary degeneration (n = 40), Pick's disease (n = 8), progressive supranuclear palsy (n = 7), corticobasal degeneration (n = 6), argyrophilic grain disease (AGD, n = 18), globular glial tauopathy (n = 5), and tau-astrogliopathy of the elderly (n = 10). AT8 immunoreactivity patterns were compared by mathematical analysis. Results: Our study reveals disease-specific hot spots and regional selective vulnerability for these disorders. The pattern of hippocampal AD-related tau pathology is strongly influenced by concomitant AGD. Mathematical analysis reveals that hippocampal involvement in primary tauopathies is distinguishable from early-stage AD-related neurofibrillary degeneration. Conclusion: Our data demonstrate disease-specific AT8 immunoreactivity patterns and hot spots in the hippocampus even in tauopathies, which primarily do not affect the hippocampus. These hot spots can be shifted to other regions by the co-occurrence of tauopathies like AGD. Our observations support the notion that globular glial tauopathies and tau-astrogliopathy of the elderly are distinct entities.

Random matrices, log-gases and Hölder regularity - Erdös, László (Proceedings of the International Congress of Mathematicians)
The Wigner-Dyson-Gaudin-Mehta conjecture asserts that the local eigenvalue statistics of large real and complex Hermitian matrices with independent, identically distributed entries are universal in a sense that they depend only on the symmetry class of the matrix and otherwise are independent of the details of the distribution. We present the recent solution to this half-century old conjecture. We explain how stochastic tools, such as the Dyson Brownian motion, and PDE ideas, such as De Giorgi-Nash-Moser regularity theory, were combined in the solution. We also show related results for log-gases that represent a universal model for strongly correlated systems. Finally, in the spirit of Wigner’s original vision, we discuss the extensions of these universality results to more realistic physical systems such as random band matrices.

Structure of the excitation spectrum for many-body quantum systems - Seiringer, Robert (Proceeding of the International Congress of Mathematicans)
Many questions concerning models in quantum mechanics require a detailed analysis of the spectrum of the corresponding Hamiltonian, a linear operator on a suitable Hilbert space. Of particular relevance for an understanding of the low-temperature properties of a system is the structure of the excitation spectrum, which is the part of the spectrum close to the spectral bottom. We present recent progress on this question for bosonic many-body quantum systems with weak two-body interactions. Such system are currently of great interest, due to their experimental realization in ultra-cold atomic gases. We investigate the accuracy of the Bogoliubov approximations, which predicts that the low-energy spectrum is made up of sums of elementary excitations, with linear dispersion law at low momentum. The latter property is crucial for the superfluid behavior the system.

A PAC-Bayesian bound for Lifelong Learning - Pentina, Anastasia; Lampert, Christoph
Transfer learning has received a lot of attention in the machine learning community over the last years, and several effective algorithms have been developed. However, relatively little is known about their theoretical properties, especially in the setting of lifelong learning, where the goal is to transfer information to tasks for which no data have been observed so far. In this work we study lifelong learning from a theoretical perspective. Our main result is a PAC-Bayesian generalization bound that offers a unified view on existing paradigms for transfer learning, such as the transfer of parameters or the transfer of low-dimensional representations. We also use the bound to derive two principled lifelong learning algorithms, and we show that these yield results comparable with existing methods.

Forces driving epithelial spreading in zebrafish epiboly - Behrndt, Martin
A variety of developmental and disease related processes depend on epithelial cell sheet spreading. In order to gain insight into the biophysical mechanism(s) underlying the tissue morphogenesis we studied the spreading of an epithelium during the early development of the zebrafish embryo. In zebrafish epiboly the enveloping cell layer (EVL), a simple squamous epithelium, spreads over the yolk cell to completely engulf it at the end of gastrulation. Previous studies have proposed that an actomyosin ring forming within the yolk syncytial layer (YSL) acts as purse string that through constriction along its circumference pulls on the margin of the EVL. Direct biophysical evidence for this hypothesis has however been missing. The aim of the thesis was to understand how the actomyosin ring may generate pulling forces onto the EVL and what cellular mechanism(s) may facilitate the spreading of the epithelium. Using laser ablation to measure cortical tension within the actomyosin ring we found an anisotropic tension distribution, which was highest along the circumference of the ring. However the low degree of anisotropy was incompatible with the actomyosin ring functioning as a purse string only. Additionally, we observed retrograde cortical flow from vegetal parts of the ring into the EVL margin. Interpreting the experimental data using a theoretical distribution that models the tissues as active viscous gels led us to proposen that the actomyosin ring has a twofold contribution to EVL epiboly. It not only acts as a purse string through constriction along its circumference, but in addition constriction along the width of the ring generates pulling forces through friction-resisted cortical flow. Moreover, when rendering the purse string mechanism unproductive EVL epiboly proceeded normally indicating that the flow-friction mechanism is sufficient to drive the process. Aiming to understand what cellular mechanism(s) may facilitate the spreading of the epithelium we found that tension-oriented EVL cell divisions limit tissue anisotropy by releasing tension along the division axis and promote epithelial spreading. Notably, EVL cells undergo ectopic cell fusion in conditions in which oriented-cell division is impaired or the epithelium is mechanically challenged. Taken together our study of EVL epiboly suggests a novel mechanism of force generation for actomyosin rings through friction-resisted cortical flow and highlights the importance of tension-oriented cell divisions in epithelial morphogenesis.

Soziale Immunität: Wie sich der Staat gegen Pathogene wehrt Bayerische Akademie der Wissenschaften - Cremer, Sylvia (Soziale Insekten in einer sich wandelnden Welt)
Im Rahmen meiner Arbeit mit der kollektiven Krankheitsabwehr in Ameisengesellschaften interessiert mich vor allem, wie sich die Kolonien als Ganzes gegen Krankheiten wehren können. Warum ist dieses Thema der Krankheitsdynamik in Gruppen so wichtig? Ein Vergleich von solitär lebenden Individuen mit Individuen, die in sozialen Gruppen zusammenleben, zeigt die Kosten und die Vorteile des Gruppenlebens: Einerseits haben Individuen in sozialen Gruppen aufgrund der hohen Dichte, in der die Tiere zusammenleben, den hohen Interaktionsraten, die sie miteinander haben, und der engen Verwandtschaft, die sie verbindet, ein höheres Ansteckungsrisiko. Andererseits kann die individuelle Krankheitsabwehr durch die kollektive Abwehr in den Gruppen ergänzt werden.

Sphere packing with limited overlap - Iglesias Ham, Mabel; Kerber, Michael; Uhler, Caroline (arXiv)
The classical sphere packing problem asks for the best (infinite) arrangement of non-overlapping unit balls which cover as much space as possible. We define a generalized version of the problem, where we allow each ball a limited amount of overlap with other balls. We study two natural choices of overlap measures and obtain the optimal lattice packings in a parameterized family of lattices which contains the FCC, BCC, and integer lattice.

On the mass concentration for Bose-Einstein condensates with attractive interactions - Guo, Yujin; Seiringer, Robert (Letters in Mathematical Physics)
We consider two-dimensional Bose-Einstein condensates with attractive interaction, described by the Gross-Pitaevskii functional. Minimizers of this functional exist only if the interaction strength a satisfies Mathematical expression, where Q is the unique positive radial solution of Mathematical expression in Mathematical expression. We present a detailed analysis of the behavior of minimizers as a approaches a*, where all the mass concentrates at a global minimum of the trapping potential.

Searching for collective behavior in a large network of sensory neurons - Tkacik, Gasper; Marre, Olivier; Amodei, Dario; Schneidman, Elad; Bialek, William; Berry, Michael (PLoS Computational Biology)
Maximum entropy models are the least structured probability distributions that exactly reproduce a chosen set of statistics measured in an interacting network. Here we use this principle to construct probabilistic models which describe the correlated spiking activity of populations of up to 120 neurons in the salamander retina as it responds to natural movies. Already in groups as small as 10 neurons, interactions between spikes can no longer be regarded as small perturbations in an otherwise independent system; for 40 or more neurons pairwise interactions need to be supplemented by a global interaction that controls the distribution of synchrony in the population. Here we show that such “K-pairwise” models—being systematic extensions of the previously used pairwise Ising models—provide an excellent account of the data. We explore the properties of the neural vocabulary by: 1) estimating its entropy, which constrains the population's capacity to represent visual information; 2) classifying activity patterns into a small set of metastable collective modes; 3) showing that the neural codeword ensembles are extremely inhomogenous; 4) demonstrating that the state of individual neurons is highly predictable from the rest of the population, allowing the capacity for error correction.

Organisational immunity in social insects - Stroeymeyt, Nathalie; Casillas Perez, Barbara E; Cremer, Sylvia (Current Opinion in Insect Science)
Selection for disease control is believed to have contributed to shape the organisation of insect societies — leading to interaction patterns that mitigate disease transmission risk within colonies, conferring them ‘organisational immunity’. Recent studies combining epidemiological models with social network analysis have identified general properties of interaction networks that may hinder propagation of infection within groups. These can be prophylactic and/or induced upon pathogen exposure. Here we review empirical evidence for these two types of organisational immunity in social insects and describe the individual-level behaviours that underlie it. We highlight areas requiring further investigation, and emphasise the need for tighter links between theory and empirical research and between individual-level and collective-level analyses.

Stimfit: A fast visualization and analysis environment for cellular neurophysiology - Schlögl, Alois; Jonas, Peter M; Schmidt-Hieber, C.; Guzman, S. J. (Biomedical Engineering / Biomedizinische Technik)
Stimfit is a free cross-platform software package for viewing and analyzing electrophysiological data. It supports most standard file types for cellular neurophysiology and other biomedical formats. Its analysis algorithms have been used and validated in several experimental laboratories. Its embedded Python scripting interface makes Stimfit highly extensible and customizable.
Keywords: biomedical engineering; data analysis; free software

Calcium: The missing link in auxin action - Vanneste, Steffen; Friml, Jiří (Plants)
Due to their sessile lifestyles, plants need to deal with the limitations and stresses imposed by the changing environment. Plants cope with these by a remarkable developmental flexibility, which is embedded in their strategy to survive. Plants can adjust their size, shape and number of organs, bend according to gravity and light, and regenerate tissues that were damaged, utilizing a coordinating, intercellular signal, the plant hormone, auxin. Another versatile signal is the cation, Ca2+, which is a crucial second messenger for many rapid cellular processes during responses to a wide range of endogenous and environmental signals, such as hormones, light, drought stress and others. Auxin is a good candidate for one of these Ca2+-activating signals. However, the role of auxin-induced Ca2+ signaling is poorly understood. Here, we will provide an overview of possible developmental and physiological roles, as well as mechanisms underlying the interconnection of Ca2+ and auxin signaling.
Keywords: Plant Science; Ecology; Ecology; Evolution; Behavior and Systematics

Distributed queues in shared memory: Multicore performance and scalability through quantitative relaxation - Haas, Andreas; Lippautz, Michael; Henzinger, Thomas A; Payer, Hannes; Sokolova, Ana; Kirsch, Christoph M.; Sezgin, Ali (Proceedings of the ACM International Conference on Computing Frontiers - CF '13)
A prominent remedy to multicore scalability issues in concurrent data structure implementations is to relax the sequential specification of the data structure. We present distributed queues (DQ), a new family of relaxed concurrent queue implementations. DQs implement relaxed queues with linearizable emptiness check and either configurable or bounded out-of-order behavior or pool behavior. Our experiments show that DQs outperform and outscale in micro- and macrobenchmarks all strict and relaxed queue as well as pool implementations that we considered.

Differentiation - Barton, Nicholas H (Encyclopedia of Biodiversity)
Keywords: Adaptive landscape; Cline; Coalescent process; Gene flow; Hybrid zone; Local adaptation; Natural selection; Neutral theory; Population structure; Speciation

Infinite-state games with finitary conditions - Chatterjee, Krishnendu; Fijalkow, Nathanaël (22nd EACSL Annual Conference on Computer Science Logic)
We study two-player zero-sum games over infinite-state graphs equipped with ωB and finitary conditions. Our first contribution is about the strategy complexity, i.e the memory required for winning strategies: we prove that over general infinite-state graphs, memoryless strategies are sufficient for finitary Büchi, and finite-memory suffices for finitary parity games. We then study pushdown games with boundedness conditions, with two contributions. First we prove a collapse result for pushdown games with ωB-conditions, implying the decidability of solving these games. Second we consider pushdown games with finitary parity along with stack boundedness conditions, and show that solving these games is EXPTIME-complete.

Synthesizing multiple boolean functions using interpolation on a single proof - Hofferek, Georg; Gupta, Ashutosh; Könighofer, Bettina; Jiang, Jie; Bloem, Roderick (2013 Formal Methods in Computer-Aided Design)
It is often difficult to correctly implement a Boolean controller for a complex system, especially when concurrency is involved. Yet, it may be easy to formally specify a controller. For instance, for a pipelined processor it suffices to state that the visible behavior of the pipelined system should be identical to a non-pipelined reference system (Burch-Dill paradigm). We present a novel procedure to efficiently synthesize multiple Boolean control signals from a specification given as a quantified first-order formula (with a specific quantifier structure). Our approach uses uninterpreted functions to abstract details of the design. We construct an unsatisfiable SMT formula from the given specification. Then, from just one proof of unsatisfiability, we use a variant of Craig interpolation to compute multiple coordinated interpolants that implement the Boolean control signals. Our method avoids iterative learning and back-substitution of the control functions. We applied our approach to synthesize a controller for a simple two-stage pipelined processor, and present first experimental results.

Nondeterminism in the presence of a diverse or unknown future - Boker, Udi; Kuperberg, Denis; Kupferman, Orna; Skrzypczak, Michał
Choices made by nondeterministic word automata depend on both the past (the prefix of the word read so far) and the future (the suffix yet to be read). In several applications, most notably synthesis, the future is diverse or unknown, leading to algorithms that are based on deterministic automata. Hoping to retain some of the advantages of nondeterministic automata, researchers have studied restricted classes of nondeterministic automata. Three such classes are nondeterministic automata that are good for trees (GFT; i.e., ones that can be expanded to tree automata accepting the derived tree languages, thus whose choices should satisfy diverse futures), good for games (GFG; i.e., ones whose choices depend only on the past), and determinizable by pruning (DBP; i.e., ones that embody equivalent deterministic automata). The theoretical properties and relative merits of the different classes are still open, having vagueness on whether they really differ from deterministic automata. In particular, while DBP ⊆ GFG ⊆ GFT, it is not known whether every GFT automaton is GFG and whether every GFG automaton is DBP. Also open is the possible succinctness of GFG and GFT automata compared to deterministic automata. We study these problems for ω-regular automata with all common acceptance conditions. We show that GFT=GFG⊃DBP, and describe a determinization construction for GFG automata.

Geometry of the faithfulness assumption in causal inference - Uhler, Caroline; Raskutti, Garvesh; Bühlmann, Peter; Yu, Bin (The Annals of Statistics)
Many algorithms for inferring causality rely heavily on the faithfulness assumption. The main justification for imposing this assumption is that the set of unfaithful distributions has Lebesgue measure zero, since it can be seen as a collection of hypersurfaces in a hypercube. However, due to sampling error the faithfulness condition alone is not sufficient for statistical estimation, and strong-faithfulness has been proposed and assumed to achieve uniform or high-dimensional consistency. In contrast to the plain faithfulness assumption, the set of distributions that is not strong-faithful has nonzero Lebesgue measure and in fact, can be surprisingly large as we show in this paper. We study the strong-faithfulness condition from a geometric and combinatorial point of view and give upper and lower bounds on the Lebesgue measure of strong-faithful distributions for various classes of directed acyclic graphs. Our results imply fundamental limitations for the PC-algorithm and potentially also for other algorithms based on partial correlation testing in the Gaussian case.